(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
The article presents the dynamics of the gross regional product, the dynamics of economic activity of the regions of the South of Russia for the period 2016-2020, the sectoral structure of the gross value added of the regions in 2020 is calculated. The authors ranked the regions of the South of Russia according to the growth rate of the gross regional product, the main trends were established socio-economic development of the South Russian macro-region at the present stage. The results of the study can be used by federal and regional government authorities in the development of strategies and programs for territorial development.